Drug Repurposing: Tolfenamic Acid Inactivates PrbP, a Transcriptional Accessory Protein in Liberibacter asiaticus - Gardner, Christopher L.; Pagliai, Fernando A.; Pan, Lei; Bojilova, Lora; Torino, Maria I.; Lorca, Graciela L.; Gonzalez, Claudio F. (Frontiers in Microbiology, 2016)
CLIBASIA_01510, PrbP, is a predicted RNA polymerase binding protein in Liberibacter asiaticus. PrbP was found to regulate expression of a small subset of ribosomal genes through interactions with the β-subunit of the RNA polymerase and a short, specific sequence on the promoter region. Molecular screening assays were performed to identify small molecules that interact with PrbP in vitro. Chemical hits were analyzed for therapeutic efficacy against L. asiaticus via an infected leaf assay, where the transcriptional activity of L. asiaticus was found to decrease significantly after exposure to tolfenamic acid. Similarly, tolfenamic acid was found to inhibit L. asiaticus infection in highly symptomatic citrus seedlings. Our results indicate that PrbP is an important transcriptional regulator for survival of L. asiaticus in planta, and the chemicals identified by molecular screening assays could be used as a therapeutic treatment for huanglongbing disease.